Synthesis, characterization and optical properties of silver and gold nanowires embedded in mesoporous MCM-41 - Adhyapak, Parag V.; Karandikar, Prashant R.; Dadge, Jagdish W.; Aiyer, Rohini C.; Chandwadkar, Asha J. (Central European Journal of Chemistry, 2006)
Uniform nanowires of silver and gold inside the channels of MCM-41 were prepared by controlled reduction of their respective metal salts with sodium borohydride (NaBH4). Presence of nanowires of silver and gold in MCM-41 were confirmed by high angle X-ray diffraction (XRD) data (peaks between 2 theta = 30 - 60 degrees) and transmission electron microscopy (TEM) confirmed the diameter of the nanowires. Diameter of nanowires is found to be similar to 2.8 nm which is coincident with channel diameter of MCM-41. Optical properties of these heterostructured materials Ag-MCM-41 and Au-MCM-41 reveals the presence of surface plasmon absorption peaks of silver and gold respectively, and the shift in the absorption bands are associated to agglomeration of clusters inside the channels. Room temperature photoluminescence spectra exhibits interesting optical properties as observed for direct band gap semiconductors. Non-linear optical properties (NLO) corresponding to second harmonic generation (SHG) values were also recorded for self supported films of these heterostructured materials. Enhanced optical non-linearity was found to be arising from a corresponding increase of local field near the surface plasmon resonance. Further enhancement in SHG was found with poling due to an induction of orientation order. (C) Versita Warsaw and Springer-Verlag Berlin Heidelberg. All rights reserved.
Keywords: Ag/Au nanowires; MCM-41; photoluminescence; SHG; TEM

Studies on the feasibility of recycled polystyrene doped with NLO active meta-Nitroaniline for optoelectronics applications - Sureshkumar, M. S.; Goyal, R. K.; Negi, Y. S.; Pratheepkumar, A.; Reddy, K. Raghunatha; Singh, R. P.; Dadge, Jagdish W.; Aiyer, Rohini C. (Polymers for Advanced Technologies, 2011)
A Guest-Host system based on meta-Nitroaniline (m-NA) and recycled polystyrene (RPS) susceptible to generate nonlinear optically (NLO) active property such as second harmonic generation (SHG) has been prepared. Pure, sublimed, optical grade, crystalline m-NA is used as a guest and RPS from the disposable packaging waste as available utilized as the host polymer. In this paper we report the effect of NLO active m-NA on the bulk and optical properties of RPS. The purified m-NA was incorporated from 1-10 wt% in the RPS polymer matrix by conventional solution casting method. Thin, transparent, freestanding films obtained were characterized with optical microscope, scanning electron microscope (SEM), viscosity measurement, and UV-Visible (UV-Vis) spectroscopy for bulk properties evaluation and Nd:YAG laser studies for optoelectronics application such as SHG through frequency doubling. Copyright (C) 2010 John Wiley & Sons, Ltd.
Keywords: frequency doubling; guest-host NLO systems; meta-Nitroaniline; nonlinear optical activity; Polystyrene; second harmonic generation

Green synthesis of polysaccharide stabilized gold nanoparticles: chemo catalytic and room temperature operable vapor sensing application - Tagad, Chandrakant K.; Rajdeo, Kishor S.; Kulkarni, Atul; More, Pooja; Aiyer, Rohini C.; Sabharwal, Sushma G. (RSC Advances, 2014)
A facile, one pot, completely green, and cheap route for the synthesis of gold nanoparticles (AuNPs) has been developed by using locust bean gum (LBG), both as a reducing and a stabilizing agent. Synthesized AuNPs were characterized by UV-vis spectroscopy, TEM, XRD, dynamic light scattering analysis (DLS) and EDAX. A characteristic surface plasmon peak at 537 nm confirmed the formation of AuNPs. Synthesized AuNPs were found to be an efficient catalyst for the reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP). The reaction follows pseudo-first order kinetics with a rate constant of 14.46 X 10(-2) min(-1). Furthermore, the catalytic efficiency of AuNPs for ethanol vapor sensing was investigated by doping AuNPs in a tin oxide (SnO2) matrix synthesized by a single step thermal decomposition method. The AuNPs doped SnO2 sensor showed a fast response (similar to 5 seconds) and excellent ethanol sensing behavior in the range of 10 to 120 ppm at room temperature. A two fold increase in ethanol vapor sensing response was observed with AuNPs doped SnO2 as compared with the pure SnO2 sensor.